Determinants of foreign direct investment in UAE. (1st November 2007) - Anwar, Syed Aziz
In view of the economic diversification process taking place with considerable speed in United Arab Emirates (UAE), the question of attracting foreign direct investment (FDI) has come into sharper focus. In fact, policymakers in the UAE consider FDI inflows as an index of the success of their international business regimes. This paper examines and analyses evidence pertaining to FDI in the UAE. It is argued that the process of economic integration leading to a customs union in 2003 in the Gulf Co-operation Council (GCC) countries creates external pressures to enhance competitiveness. This kind of pressure is actually in the interest of the UAE seeking to compete in international markets. Based on evidence, the paper goes on to identify the determinants of FDI in the UAE. While most of the determinants identified in the paper are in line with conventional wisdom and earlier research studies, it is argued that their hierarchical importance is context-specific.